2020
DOI: 10.9734/ajfar/2020/v8i330140
|View full text |Cite
|
Sign up to set email alerts
|

The Environmental Friendliness Level of Boat Bagan Fishing Gear in Belitung Regency

Abstract: This research aimed to analyze the environmental friendliness level of boar bagan towards the amount of fish caught by the fishermen in Belitung Regency Waters and determined fish composition based on the type and the length of fish. The research was conducted in August 2019. The primary data collection technique used was purposive sampling technique while the secondary data was obtained from Tanjungpandan Archipelago Fisheries Port (Pelabuhan Perikanan Nusantara Tanjungpandan/PPN). The research analyzed types… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Meanwhile, the other dominant fish catches are Decapterus ruselli, Rastrelliger canagurta, Sardinella fimbriata, and Leiognatus aureus. While the research of Tejo et al (2020) showed that the catch of boat lift nets in Belitung District waters is Sardinella fimbriata, Sardinella sirm, Stolephorus devisi, Loligo sp., Rastrelliger brachysoma, Leiognathus equulus, Trichiurus sp., Selaroides leptolesis, Sphyraena sp., and Tetraodo sp.…”
Section: A B Cmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, the other dominant fish catches are Decapterus ruselli, Rastrelliger canagurta, Sardinella fimbriata, and Leiognatus aureus. While the research of Tejo et al (2020) showed that the catch of boat lift nets in Belitung District waters is Sardinella fimbriata, Sardinella sirm, Stolephorus devisi, Loligo sp., Rastrelliger brachysoma, Leiognathus equulus, Trichiurus sp., Selaroides leptolesis, Sphyraena sp., and Tetraodo sp.…”
Section: A B Cmentioning
confidence: 99%
“…The research of Tejo et al (2020) showed that the boat lift net is classified as less environmentally friendly because 48% of fish caught is not mature. According to Solomon and Ahmed (2016), the use of artificial light can attract fish and increase fish catches, but it can also deplete fish resources and degrade coral reefs.…”
Section: A B Cmentioning
confidence: 99%